Phytotoxic Effect of Tree Leave and Bark: On Germination and Seedling Growth of Some Traditional Summer Food Crops of Garhwal Himalaya - Dhanai, C.S.; Singh, Bhupendra; Todaria, N.P. (Indian Journal of Agroforestry, 2020)
In the context of the present investigation it is pertinent to mention that investigated tree crops are used extensively as multipurpose farm trees in Garhwal Himalaya. Toxic effect of leaf and bark extract of these agroforestry tree species on germination and growth of food crops have been investigated. Leaves as well as barks extract equally inhibited germination and growth of test crops. The foliage and bark extract of G. oppositifolia and F. roxburghii were most toxic and E. frumentaceae as the most susceptible of the agricultural crops tested, whereas G. max showed some resistance. Among the test crops, the most resistant and versatile was E. coracana and the most susceptible was E. frumentaceae; P. mungo behaved in between the two extremes.